Odpowiedzi

Najlepsza Odpowiedź!
2010-01-11T20:30:14+01:00
A) x + 2y = -2
2x - y = 1

x=-2-2y
2*(-2-2y)-y=1

x=-2-2y
-4-4y-y=1

x=-2-2y
-5y=5 /:-5

x=-2-2y
y=-1

x=-2-2 * -1
y=-1

x=0
y=-1


b) x + 4y = -2
3x - 8y = 10

x=-2-4y
3*(-2-4y)-8y=10

x=-2-4y
-6-8y-8y=10

x=-2-4y
-16y=16/:-16

x=-2-4y
y=-1

x=-2-4*-1
y=-1

x=2
y=-1


c) x - 2y = 3
-2x + y = 0

x=3+2y
-2*(3+2y)+y=0

x=3+2y
-6-4y+y=0

x=3+2y
-3y=6/: -3

x=3+2y
y=-2

x=3+2*-2
y=-2

x=-1
y=-2


ale się napisałem licze na naj ;p
23 4 23
  • Użytkownik Zadane
2010-01-11T20:32:34+01:00
A) x+2y= -2
2x- y= 1

x+2y= -2 /*-2
2x-y=1

-2x-4y=4
2x-y=1

-5y = 5
-y=1
y= -1

b) x+4y=-2
3x-8y=10

x+4y= -2 /*-3
3x-8y=10

-3x-12y = 6
3x- 8y= 10

-20y = 16 /:20

-y= 4/5
y= -4/5

c) x-2y=3
-2x+y =0

x-2y=3 /*2
-2x+y=0

2x-4y=6
-2x+y=0

-3y=6 /:3

-y=2

y= -2

5 4 5
2010-01-11T20:33:49+01:00